About Late Gagary-Ostrovian biota (Late Permian) at the North of the Siberian platform - G. N. Sadovnikov (Известия высших учебных заведений: Геология и разведка)
Prior to the beginning of a trap volcanism of Central Siberia there was a plain, covered by Cordaitanthales. Slope herbaceous cover consisted mainly of ferns. Equisetopsida prevailed in the swampy lowlands. Volcanic eruptions at the end of Vishkilian (Severodvinian) led to the formation of a hill. It was covered by similar vegetation, but vegetation of herbaceous slopes substantially prevailed. Woody vegetation was dominated at only two locations, it was also about 50% at three locations and absent at two ones. Associations of the grassy slopes in most places were at least 46%, they were about 100% in two places and absent in 42% of the places. Ferns dominated sharply. Todites (?) anthriscifolia, Todites (?) sibirica, Prynadaeopteris (?) karpovii, rarely Cladophlebis aff. taimyrensis were dominants. Sometimes Prynadaeopteris (?) venusta were codominants. Yavorskyia radczenkovii sometimes codominated among gymnosperms. The herbaceous cover of the lowlands was dominated by Equisetopsida. At two locations, they are about 100%, and more than 50% at two ones , and from 12 to 33% at four ones. They are absent only at two localities. Paracalamites were usually dominants. Sometimes hyllotheca turnaensis, P. minuta, Paraschizoneura codominated. In the basins, Palaeoanodonta (Bivalve) had a significant role. Thus, the composition of the flora of the Late Gagary-Ostrovian time has a little difference from the Early Gagary-Ostrovian, but the ecological differences are significant. Forest communities are inferior to the dominant role of herbaceous slopes ones. This makes the flora of the Late Gagary-Ostrovian time be similar to the followed Tutonchanian - Early Dvurogyan flora in the ecological sense.